Cyberjaya, Malaysia: Bridging the Gap Between User Acceptance and the 5G Technology Readiness - Tasmin, Rosmaini; Lim, Jea Yi; Abu Bakar, Suwaibah (Research in Management of Technology and Business, 2023)
5G technology is the fifth generation of mobile networks inspired by the 4.0 Industrial Revolution’s expanding capacity requirements for increased speed, broad coverage, and reliable security. It is much more than a fast mobile internet connection that allows for the consumption of copious amounts of data-based content. The primary concern of 5G in this study is the second-lowest download speed of 13.5 Mbps after the launch of 5G in Malaysia. This issue may affect user readiness and acceptance of 5G technology. The primary purpose is to identify the variables that influence user acceptance of 5G technology readiness in Cyberjaya. This study employed a quantitative methodology to collect secondary data from related publications. Via a quantitative research methodology, data were gathered from 382 members of the target population using a web-based survey questionnaire. To meet the aims of this research, descriptive statistics analysis and inferential statistics analysis are utilised to analyse the data. The study reveals the aspects that determine the 5G technology readiness of users. In addition, the study revealed that elements of user approval such as Performance Expectation, Effort Expectation, and Social Influence exist. The inability to generalise the findings to different mobile networks was one of the constraints of this study. Therefore, it was suggested that future researchers examine several forms of mobile networks to better comprehend the topic. This study’s findings can lead to a greater comprehension of the viewpoints on user acceptance of 5G technology.